I am Deaf - Makarov, Nickolay (Russia, 2005)
In this film deaf people tell about themselves: how they hear and talk, how many different sign languages exist, why they do not think they are invalids and how sociable they are living in the world of their own. We watch children learning how to communicate with hearing people and with the world full of sounds. The heroes of the film are an artist and an actor Alexander Martiamov, a journalist and a writer Victor Palenyj, the students of the Academy of Arts for the disabled, the pupils and the teachers of special schools, deaf workers from the Admiralty shipyards, the members of an Orthodox community. This film is destined not only for hearing people and is not only about the deaf, it is about the necessity of understanding each other...
Verzio Film Festival Submission
Keywords: Documentary films